Documenta 1955 : Erste Internationale Kunstausstellung - eine fotografische Rekonstruktion - Kimpel, Harald; Stengel, Karin; Stadt Kassel; documenta Archiv, Kassel; Documenta 1955 (Bremen : Edition Temmen, 1995)
Lehmbrück, Wilhelm ; Blumenthal, Hermann ; Calder, Alexander ; Pevsner, Antoine ; Beckmann, Max ; Chagall, Marc ; Barlach, Ernst ; Picasso, Pablo ; Matisse, Henri ; Rousseau, Henri
boek